Effect of Participation in General Skills Training, Job Satisfication, and Perceived Organizational Support and Job Burn Out on Turnover Intention : Financial Technology Employees in Jakarta - Oka Triani, Elza; Emilisia, Netania; Puspa, Tiara (Jurnal Ecoment Global, 2023)
Objective: This study aims to find the influence between Participation in General Skills Training, Job Satisfaction, and Perceived Organizational Support and Job Burn Out on Turnover Intention in Financial Technology Employees in Jakarta. Design/Methods/Approach: Data were analyzed using structural equation models and SPSS model-21. This research focuses on a number of Financial Technology workers in Jakarta, with a total sample of 165 respondents obtained by questionnaire with purposive sampling technique. The data obtained was processed using SPSS software to test validity, reliability and hypotheses. Findings: The results showed that there was a significant positive influence between Participation in General Skills Training, Job Satisfaction, and Perceived Organizational Support and Job Burn Out on Turnover Intention. Originality/Value: This research design was conducted with quantitative survey methods used on a sample of 147 early career graduate trainees in China. The data were analyzed using structural equation models and model-21 in the PROCESS macro for SPSS. Practical/Policy implication: This research is expected to provide input for company managers to maximize effectiveness by modifying or designing work to work more effectively.